SEMINAR MICROSOFT WORD DALAM MENINGKATKAN SKILL ADMINISTRASI SURAT MENYURAT DI SMPN 1 ARJASA - Zaehol Fatah; Sitti Hafidzaturrafiah (CV. Denasya Smart Publisher, 2026)
The ability to manage incoming abd outgoing correspondence is an essential skill in educational environments, as it ensures that all school activities run smoothly. However, challenges remain in mastering proper writing techniques and effective document management, both among administrative staff and students. This study aims to examine how effectively a Microsoft Word seminar can improve correspondence management skills at SMPN 1 Arjasa. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that the seminar had a positive impact on participants’ understanding of various Microsoft Word features, including creating formal letters, document layout, and applying templates in accordance with administrative standars. Additionally, participants showed improvement in their ability to produce well-structured and proffessional official letters. Therefore, the Microsoft Word seminar can be considered and effective approach to enhancing correspondence management skills in the school anvironment.